MANAGING CHANGE THROUGH LEADERSHIP DEVELOPMENT PROGRAM: SOCIAL PSYCHOLOGICAL APPROACH An experience from FT. Caltex Pacific Indonesia - Djamaludin Ancok (Faculty of Economics and Business, Universitas Gadjah Mada, 1997)
The changes in the business environment may bring a company into a dangerous situation if the company does not react properly to the changes. In order to successfully coping with the change, a number of companies have taken several measures to improve the performance, either by restructuring, or reengineering their organization. Usually there are two areas of changes that take the attention of management. Firstly, the changes in shared vision, business strategy, structure, and system of organization. Secondly, the change in human behavior of organization, which consists of staff, skill, and style. Pascale and A thos (1981) in their se ven S model of chronic organization, called the former as the hard S while the latter they called soft 5. No matter how excellent are the business strategy, structure and system, the changes in an organization would not occur unless there are changes in human behavior. This paper discusses the effort to change the behavior, with specialemphasis on leader behavior. A case study from an oil company, Caltex Pacific Indonesia (CPI) which is in the process of restructuring, would be utilized as an illustration of the effort to change the organization through leadership development program. In CPI a massive leadership development program has been launched to speed up the process of change. The program covers all layers of leaders, starting from the bottom layer up to the top management level. The bottom layer focuses on transformational leadership, the second upper layer stresses on synergistic leadership, and the top layer concentrates on visionaryleadership. Based on qualitative data found from a preliminary study aimed at assessing the impacts of the program in speeding up the change in CPI, it was found that the CLD program has contributed positively to the change process.